Encyclopedia of Inorganic Chemistry 2005
DOI: 10.1002/0470862106.ia129
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Proteins with Mono‐ & Dinuclear Sites

Abstract: Although manganese is not as widely recognized as iron and copper, it nevertheless plays an essential role in several key biological processes. Consequently, manganese concentrations are tightly regulated in most cells. Several Mn‐specific transporters have been identified and a novel Mn‐regulatory protein has been characterized. Manganese‐activated enzymes are proteins that have relatively weak affinities for Mn; in many cases these are isolated without any metal bound. Manganese‐activated enzymes are especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…Electronic coupling is treated as in electron-transfer theory as an electrostatic perturbation that leads to donoracceptor electronic wave function mixing. The resulting resonance energy, the electron-transfer matrix element V ET , is given by Equation (13) in which y A and y D are the electronic wave functions for the acceptor and donor orbitals, respectively, and H is the operator mixing the states.…”
Section: Theory Of Coupled Electron-proton Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic coupling is treated as in electron-transfer theory as an electrostatic perturbation that leads to donoracceptor electronic wave function mixing. The resulting resonance energy, the electron-transfer matrix element V ET , is given by Equation (13) in which y A and y D are the electronic wave functions for the acceptor and donor orbitals, respectively, and H is the operator mixing the states.…”
Section: Theory Of Coupled Electron-proton Transfermentioning
confidence: 99%
“…From earlier EXAFS results on S 1 , it was proposed that the OEC is composed of two to three di-m-oxido Mn units with Mn···Mn separation distances of around 2.7 . [9,13,[148][149][150][151] A recent extended range EXAFS study on S 1 revealed three Mn···Mn vectors in the {CaMn 3 } cluster, two of around 2.7 and one of approximately 2.8 , as well as another one or two Mn···Mn interactions with a separation of 3.3 . [152] Even more recently, the structure of S 1 was investigated by EXAFS measurements on single crystals free of radiation damage.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure , in the sequence of reactions following formation of 1 P 680 *, without histidine electron transfer is highly unfavorable. Oxidation of tyrosine is too slow to compete with back electron transfer from Q A •– to P 680 •+ . ,, With His(190) in place and MS-EPT available, the energetics are favorable by ∼0.2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese­(II), being an integral part of Mn­(II)-POR, plays a major role in different biological processes, most notably glutamine synthetase in astrocytes of the human brain. Enzymes requiring manganese as a cofactor are typically large and include different classes of enzymes including oxidoreductases, transferases, hydrolases, lyases, isomerases, ligases, lectins, and integrins. , Typical examples are reverse transcriptases of many retroviruses (though not lentiviruses such as HIV), arginases, the diphtheria toxin, , and Mn-containing superoxide dismutase (Mn-SOD). ,, A number of experimental and theoretical studies were carried out to investigate manganese containing biomolecules. Theoretical methods provided insights into Mn-containing molecules, but their applications are limited by the lack of adequate force-field parameters required for the evaluation of physiochemical properties (e.g., via molecular dynamics simulations). In many cases, the problem of missing force-field parameters for manganese-containing systems is resolved by simply utilizing the parameters of a magnesium ion instead because both share a similar coordination pattern.…”
Section: Introductionmentioning
confidence: 99%